UPAYA GURU MENGAJI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN PADA ANAK USIA 6-7 TAHUN DI DESA MERPATI DUSUN PAUH KECAMATAN TANGARAN - Kiki Sundari (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2015)
The efforts of the Koran teacher in improving the ability to read the Qur'an in children aged 6-7 years are carried out because of a decrease in the learning achievement of the Qur'an, the low ability to read the Qur'an. This study aims to clearly describe the competence of the Koran teacher in improving the ability to read the Qur'an. The method of the Koran teacher in improving the ability to read the Qur'an. Factors that influence the Koran teacher in improving the ability to read the Qur'an. This study uses a qualitative approach and the type of descriptive research. Data collection techniques using interviews, observation, documentation. The results of the study concluded that the competence of the Koran teacher was to have a good personality. Have insight and knowledge about the field of the Qur'an Mastery of the material even though it is more practice than theory. Using the method and using the media of the Iqra 'book and the index finger, pointing at the Koran and pounding your hands on the floor. The Koran teacher learns on his own, learns from cellphones through his children, and learns with others without any training. The Koran teacher and students have participated in MTQ competitions. The method of the Koran teacher is a combined method of the Jibril method, the iqra' method, the qira'ati method, and the analogy (illustration) method. The factors that influence the Koran teacher are the harmonious relationship between the Koran teacher and the child's parents, the influence of the family and community environment, time management, the lack of absorption of children, and eye health factors.